PEMBELAJARAN MENULIS PUISI DENGAN TEKNIK ONOMATOPE DI MA TANJUNGJAYA - Siti Robiah Adawiah; Leni Liani Pertiwi; Sary Sukawati; Dida Firmansyah (IKIP Siliwangi, 2019)
This research aims to determine the implementatiom of onomatope techniques on writing poetry in class of X MA Tanjungjaya. This research is done by taking the object of 27 students. The influence factor applied is onomatope techniques on poetry writing. Data were analyzed by descriptive analysis using pretest and postest. Criteria used as a judgement include themes, diction, majas, images, and mandate.Constraints faced by students, among other, themes that are not in accordance with the contents of poetry, students have not been able to use diction, students have not been able to apply majas and images, and students are still not able to discribe the mandate in writing poetry. Based preliminary and final test results can be seen on average student scores on the initial test, that is 55. While the average student scores on the final test, that is 70. The result of the study can bee concluded that the ability in class af X MA Tanjungjaya in writing poetry exparienced an increasein in the number of imsges and majas contained in the poetry, although there are still some students who have not maximized in the use of majas and images.